2006
DOI: 10.1038/sj.ki.5001521
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stem cells reduce interstitial fibrosis but do not delay progression of chronic kidney disease in collagen4A3-deficient mice

Abstract: Multipotent mesenchymal stem or stromal cells (MSC) have shown to improve outcome of acute renal injury models, but whether MSC can delay renal failure in chronic kidney disease is not known. We injected primary MSC or saline into mice that lack the alpha3-chain of type IV collagen (COL4A3), a model of chronic kidney disease with close similarities to human Alport disease. Weekly injections of MSC from week 6 to 10 of life prevented the loss of peritubular capillaries and reduced markers of renal fibrosis, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(194 citation statements)
references
References 37 publications
10
175
0
9
Order By: Relevance
“…Herein, the animals treated with MSCs showed increased expression of HGF and HO-1. HGF binds to Met, a transmembrane receptor belonging to the tyrosine kinase superfamily that inhibits the progression of fibrosis in several models, such as remnant kidney [53], unilateral ureteral obstruction [54,55], and diabetic nephropathy [56,57]. HGF expression in MSC-treated animals most likely correlates with their own secretion, as previously reported [26].…”
Section: Discussionsupporting
confidence: 61%
“…Herein, the animals treated with MSCs showed increased expression of HGF and HO-1. HGF binds to Met, a transmembrane receptor belonging to the tyrosine kinase superfamily that inhibits the progression of fibrosis in several models, such as remnant kidney [53], unilateral ureteral obstruction [54,55], and diabetic nephropathy [56,57]. HGF expression in MSC-treated animals most likely correlates with their own secretion, as previously reported [26].…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…While animal studies involving models of IR or chemically-induced AKI have shown consistent improvement after MSC delivery, their effectiveness in chronic damage models is less clear [53]. Some studies have shown improvement after MSC delivery in a model of glomerulonephropathy [54] and no evidence of a long-term fibrotic response 3 months after delivery of MSCs to animals with severe AKI [44].…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern, besides tumor formation, is development of fibrosis (Iwano et al, 2002;Russo et al, 2006), since MSCs are fibroblast-like cells and are stimulated by TGF-␤, a factor that has been shown to be the major factor in the development of tissue fibrosis. Animal models of BMDC treatment have actually shown that these cell preparations are protective of tissue fibrosis rather than profibrotic (Ortiz et al, 2003;Zhao et al, 2005;Ninichuk et al, 2006), rendering the potential contribution of MSCs to fibrosis insignificant.…”
Section: Side Effects and Dangersmentioning
confidence: 99%